Training of Brazilian Urology residents in laparoscopy: results of a national survey - Busato Junior,Wilson Francisco Schreiner (2020)
ABSTRACT Objectives To evaluate the familiarity of Brazilian urology residents with laparoscopy, methods of training and perspectives. Material and methods a questionnaire with 23 questions was sent by e-mail to all urological residents of 86 Urology Residence Programs certified by the Brazilian Society of Urology (BSU). Results 225 valid answers (85% of all residents) responded. Most residences belong to academic hospitals mainly in the Southeast region of Brazil. Women account for 5% of residents and 82% of programs perform less than 100 procedures per year. Residents have access to LESS, RAL and 98% to surgical laparoscopy and 87% of these participate actively at the surgery, but 84.9% do not have access to RAL. The most common laparoscopic procedure is radical nephrectomy (73.2%), but only 28.8% of residents acted as surgeons, and third year residents (R3) are those that mainly performed this procedure (statistical significance, p <0.05). 61% of residents do not participate in hands-on courses or fellowship in laparoscopy, among those who attended these fellowships, 23.47% were sponsored by BSU in equal regions of the country. Although there are several opportunities of training in laparoscopy, 42% of residents do not have access to any kind of preparation and 52% have no structured specific program. R3 perception of laparoscopy experience is significantly higher than R2 and R1 residents. Almost 30% of them affirms that they are prepared for professional life regarding urologic laparoscopy. Conclusion Brazilian urologic residents have access to laparoscopy and actively participate in the learning process. Robotic surgery is expanding in the country, although still very far from residents. Brazilian resident, at the end of medical residency, is motivated to perform laparoscopic procedures.